Endoscopic resection is feasible for high-grade dysplasia in patients with ulcerative colitis. (2nd January 2023) - Nishio, Masafumi; Hirasawa, Kingo; Chiba, Sawako; Ozeki, Yuichiro; Sawada, Atsushi; Ikeda, Ryosuke; Fukuchi, Takehide; Kobayashi, Ryosuke; Sato, Chiko; Inayama, Yoshiaki; Kunisaki, Reiko; Maeda, Shin
Abstract: Background: Endoscopic resection (ER) is feasible for treating well-circumscribed dysplasia in patients with ulcerative colitis (UC). However, long-term prognosis of ER for high-grade dysplasia (HGD) in patients with UC remains unclear. We aimed to evaluate the long-term prognoses of ER for HGD compared with low-grade dysplasia (LGD) and verify the feasibility of ER and follow-up with surveillance colonoscopy for HGD. Methods: An observational, single-center retrospective study included 38 and 22 patients with LGD and HGD who were followed-up with surveillance colonoscopy after ER. We evaluated the cumulative incidence rate of metachronous HGD or colorectal cancer (CRC) and identified the characteristics of metachronous dysplasia. Results: The median follow-up period was 56 months, and surveillance colonoscopies were performed 3.6 times (mean). The 5-year cumulative incidence rate of HGD/CRC was relatively high in HGD (24.6%) than in LGD (13.7%), but the difference was not significant ( p = .16). In HGD cases, six metachronous dysplasia lesions (two LGD and four HGD) were detected 11.6–40.5 months after ER. However, these patients did not progress to CRC. All metachronous lesions were well-circumscribed and with no invisible dysplasia surrounding them; they were 'endoscopically resectable' lesions. Two of the four metachronous HGD lesions were treated endoscopically and two, by colectomy. No synchronous HGD or CRC was detected in the colectomy specimens. Conclusions: Our results suggest that ER and follow-up with surveillance colonoscopy is feasible in patients with HGD when histological complete resection is achieved.